Efektifitas guru pendidikan jasmani dalam pembelajaran daring - Maftuhin, Ridwan Ahmad; Pati, Pandu Kresna; Setyawan, Danang Aji (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
The implementation of education policies during the Covid-19 pandemic caused learning activities to be carried out remotely through the network or online. Responding to the challenges of the COVID-19 pandemic, teachers are required to be able to use technology to facilitate the online learning process and change teaching as usual with virtual media. The purpose of this study is to see the effectiveness of physical education teachers in online learning. The type and approach of this research is descriptive qualitative, which was conducted at SMA Negeri 1 Semarang, SMA Negeri 11 Semarang, SMA Sedes Sapientiae, and SMA Islam Sultan Agung 1 Semarang. Data collection techniques were carried out by observation, interviews with physical education teachers and documentation. Based on the research results, zoom is considered the most effective for implementing online learning. In fact, online learning hinders the implementation of some materials in physical education learning because not all materials can be taught through online learning. The success factor of online learning is driven by the interest and ability of students to continue learning. The obstacle in this online learning is the network or connection, and students and teachers feel bored and bored if they have to deal with gadgets or laptops continuously.